Impact of salinity on the production of tomato along the coastal areas of Benin Republic - EZIN, VINCENT; Yabi, Ibouraïma; Ahanchede, Adam (My University, 2012)
The coast of Benin lies on a wide bay in the Gulf of Guinea called the Bight of Benin, about 125 km between Togo and Nigeria. The coastal areas of Benin cover part of the cultivable lands of the country. A total of 15 tomato varieties were recorded in the areas of study. The characteristics of each variety grown under salinity were also recorded based on the assessment of farmers. Salinity causes unfavorable conditions that restrain the normal crop production. The factors that contribute significantly to salinity were soil salinity, wet breeze from high tide especially between June to August and direct watering of crop with saline water. The wetted foliage of growing tomato absorbed the salts directly. The results obtained also show that salinity in the coastal areas of Benin affected tomato growth, leaf length, and number of leaves, which reduced yields and in severe cases, total yield was lost. Two varieties (aclinkon and petomèche) seemed to be tolerant to salinity because of their average yield. Due to the heavy losses in tomato production, producers were eager to be supplied with new varieties tolerant to salinity. Henceforth, it was imperative to have an evaluation of the coastal areas of Benin affected by the salinity.
Keywords: Coastal areas; tomato production; salinity; wet breeze; high tide.